Overcoming ethical and legal obstacles to data linkage in health research: stakeholder perspectives - Smit, Julie-Anne; van der Graaf , Rieke; Mostert , Menno; Vaartjes , Ilonca; Zuidgeest , Mira; Grobbee, Diederik; van Delden, Johannes J.M. (International Journal of Population Data Science, 2023)
Introduction Data linkage for health research purposes enables the answering of countless new research questions, is said to be cost effective and less intrusive than other means of data collection. Nevertheless, health researchers are currently dealing with a complicated, fragmented, and inconsistent regulatory landscape with regard to the processing of data, and progress in health research is hindered. Aim We designed a qualitative study to assess what different stakeholders perceive as ethical and legal obstacles to data linkage for health research purposes, and how these obstacles could be overcome. Methods Two focus groups and eighteen semi-structured in-depth interviews were held to collect opinions and insights of various stakeholders. An inductive thematic analysis approach was used to identify overarching themes. Results This study showed that the ambiguity regarding the `correct' interpretation of the law, the fragmentation of policies governing the processing of personal health data, and the demandingness of legal requirements are experienced as causes for the impediment of data linkage for research purposes by the participating stakeholders. To remove or reduce these obstacles authoritative interpretations of the laws and regulations governing data linkage should be issued. The participants furthermore encouraged the harmonisation of data linkage policies, as well as promoting trust and transparency and the enhancement of technical and organisational measures. Lastly, there is a demand for legislative and regulatory modifications amongst the participants. Conclusions To overcome the obstacles in data linkage for scientific research purposes, perhaps we should shift the focus from adapting the current laws and regulations governing data linkage, or even designing completely new laws, towards creating a more thorough understanding of the law and making better use of the flexibilities within the existing legislation. Important steps in achieving this shift could be clarification of the legal provisions governing data linkage by issuing authoritative interpretations, as well as the strengthening of ethical-legal oversight bodies.